Early Individualized Medical Nutrition Therapy in Recurrent Luminal B Breast Cancer Complicated by Post-Chemotherapy Febrile Neutropenia and Pancytopenia with Moderate Malnutrition: A Case Report - Arisita Andy Putri; Ni Made Dwi Asti Lestari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Breast cancer is the most common malignancy among women, and malnutrition affects approximately 30–50% of hospitalized patients with cancer, independently increasing treatment-related toxicity, prolonging hospitalization, and worsening survival. When cytotoxic chemotherapy precipitates febrile neutropenia and pancytopenia, reduced intake, systemic inflammation, and bone-marrow suppression converge, yet nutritional care is frequently deprioritized during the neutropenic nadir. Case presentation: A 58-year-old woman with recurrent left breast cancer (luminal B subtype), previously treated with mastectomy and three chemotherapy cycles, presented with two weeks of anorexia, fever (40.6 °C), vomiting, diarrhea, and 3 kg weight loss. Anthropometry showed a body mass index of 17.6 kg/m2 and a mid-upper-arm circumference of 23 cm; laboratory testing confirmed febrile neutropenia (absolute neutrophil count 0.05 ×103/µL) with pancytopenia and hypoalbuminemia (2.7 g/dL). She met three phenotypic and two etiologic Global Leadership Initiative on Malnutrition (GLIM) criteria, establishing moderate malnutrition. Alongside supportive care and granulocyte colony-stimulating factor, individualized medical nutrition therapy targeting 2,100 kcal/day and 90 g protein/day was delivered as a soft oral diet with a peptide-based oral nutritional supplement and vitamin B12. Oral intake rose from 50% or less to 86% by day three and 93% by day four; over six days, weight, appetite, physical function, and all hematologic indices recovered, and she was discharged stable. Conclusion: Early, individualized medical nutrition therapy initiated before severe malnutrition develops can support concurrent nutritional, immune, and hematologic recovery in breast cancer patients with post-chemotherapy hematologic toxicity. Routine nutritional screening and prompt, protein-focused intervention should be integrated into oncology care.